Reconsidering the usefulness of long-term high-dose buprenorphine - Jain, Lakshit; Meeks, Thomas W.; Blazes, Christopher K. (Frontiers in Psychiatry, 2024)
Buprenorphine has been successfully used for decades in the treatment of opioid use disorder, yet there are complexities to its use that warrant attention. While the package insert of the combination product buprenorphine\naloxone continues to recommend a maximum dose of 16 mg/d for maintenance, the emergence of fentanyl and synthetic analogs limits the effectiveness of this standard dose. Many practitioners have embraced and appropriately implemented novel practices to mitigate the sequelae of our current crisis, with patients commonly being stabilized with 24 - 32 mg/d of buprenorphine at initiation. Many of these patients, however, are maintained on these high doses (>16 mg/d) indefinitely, even after prolonged stability. Although this may be necessary in the short term, there is little evidence to support its safety and efficacy, and these high doses may expose patients to more complications. Commonly known side effects of buprenorphine that are likely dose-related include hyperhidrosis, sedation, decreased libido, etc. There are also complications related to the active metabolite norbuprenorphine, which is a full agonist at the mu-opioid receptor and does not have a ceiling on respiratory suppression. These can lead to medical morbidity and decreased medication adherence. We, therefore, recommend that after a period of stabilization, practitioners consider a trial of decreasing the dose toward standard recommendations. Side effects of buprenorphine may not have much salience when patients are struggling for survival and safety, but for those who are fortunate enough to advance in their recovery, the side effects can limit the quality of life and adherence.